Phenomenological Sociology Insight and Experience in Modern Society : Experience and Insight in Modern Society. - Ferguson, H. (Published in Association with Theory, Culture & Society., 2006)
This innovative and thought-provoking book argues that phenomenology was the most significant, wide-ranging and influential philosophy to emerge in the twentieth century. The social character of phenomenology is explored in its relation to the concern in twentieth century sociology with questions of modern experience. By reading phenomenology sociologically and sociology phenomenologically, this book reconstructs a phenomenological sociology of modern experience. Erudite and assured, this book opens up a series of new questions for contemporary social theory that theorists and students of theo.